To be an artist : musicians, visual artists, writers, and dancers speak - Colatosti, Camille (E L Kurdyla Publishing, 2012)
"To be an artist" is a conversation with today's successful and prominent artists from a variety of disciplines--musicians, visual artists, digital artists, poets, writers, activists and scholars. All of them discuss what it means to be an artist today, how they perceive their craft and their world, and the role of art in society. They agree that artists' creativity and success come not only from the intense focus of their craft, but, also from their development of a worldview--from their wider vision and understanding of the world in which they live."--Page 4 of cover.